Comparative emission and energy performance of biochar production versus in-situ burning of Gorean agrobyproducts - Sunyong Park; Kwang Cheol Oh; Seok Jun Kim; Padam Prasad Paudel; Seon Yeop Kim; Kyeong Sik Kang; Sunhwa Ryu; DaeHyun Kim (PLoS ONE, 2026)
Uncontrolled open-field burning of agricultural residues remains a pervasive source of air pollutants and greenhouse gases in Korea, particularly for high-burning-ratio crops such as perilla, pepper, pear, grape, and apple residues. This study provides a comprehensive assessment of the environmental and energy implications of replacing open-field burning with biochar production from these major residue streams. First, mass- and energy-normalized emission factors for CO, CH₄, CO₂, NOₓ, N₂O, and particulate matter were quantified for both in-situ combustion and biochar combustion scenarios. Although biochar exhibited higher mass-based emission factors due to carbon and nitrogen enrichment during pyrolysis, the substantially lower mass required to deliver equivalent energy output resulted in markedly reduced annual emissions. System-level calculations showed that shifting from open-field burning to biochar conversion decreased CO, CH₄, and CO₂ emissions by 40.6–46.5%, NOₓ and N₂O emissions by 29.9–92.7%, and particulate emissions by 14.7–86.6%. Energy analysis demonstrated that biochar production is energetically favorable, with energy inputs of 2.65–3.50 MJ/kg and energy return on investment (EROI) values ranging from 8.57 to 10.06, exceeding the conventional viability threshold of 3.0. Apple pruning residues showed the highest biochar and net energy potentials, corresponding to 36.45 GWh/yr of electricity generation when co-fired in existing thermal power plants. Finally, greenhouse gas impacts were evaluated using 100-year global warming potential metrics. The biochar pathway reduced annual climate impacts by approximately 192,967 tCO₂eq/yr relative to baseline burning, translating to an estimated carbon-credit benefit of 4.44 billion KRW under 2020 market conditions. Overall, the findings indicate that biochar conversion provides a viable and impactful strategy for mitigating emissions and enhancing renewable energy recovery from agricultural residues in Korea.